Redesign of A Cake Batter Mixing Machine Using A Stepped Pulley - Ramadhan, Rafli Rizki; Riandadari, Dyah; Wulandari, Diah; Sofi, Nurul Ainu (Madani: Jurnal Ilmiah Multidisiplin, 2026)
One of the key elements in making high-quality sponge cake batter is consistent and precise mixing, ensuring all ingredients are well-blended and producing the air bubbles necessary for softness. The aim of this machine redesign was to overcome the limitations of the previous design by using a multi-stage pulley. By redesigning the machine, it can be tailored to more specific operational needs, improve product quality, and minimize wasted time. To achieve this goal, the sponge cake mixer, which previously used a fixed-size pulley system, was updated to be more efficient in regulating rotation speed. Therefore, research was conducted by replacing the pulley size variations with a 5-inch diameter with 840 rpm, 6 inches with 700 rpm, and 7 inches with 600 rpm. During the testing process, the dough was mixed and the time required until the dough was ready was recorded.Based on the results of the trial using a multi-level pulley, it was found that the average time for mixing sponge cake batter with a 5-inch pulley produced an average time of 37 minutes, while a 6-inch pulley produced an average time of 46 minutes, and for a 7-inch pulley produced an average time of 55 minutes. A 5-inch diameter pulley is the appropriate size for use in a redesigned sponge cake batter mixer machine because it produces the fastest mixing time, which is an average of 37 minutes, with a rotation speed of 840 rpm. This pulley size is able to increase the efficiency of production time without reducing the quality of the dough mixing results